PENERAPAN MEDIA GAMIFIKASI TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK AUTIS KELAS RENDAH DI SEKOLAH LUAR BIASA - PUTRI, AISYAH (Jurnal Pendidikan Khusus, 2017)
Abstract: This research is motivated by the importance of improving reading ability in autistic children who experience barriers to read the beginning. This is seen in the ability to read the beginning of children with autism includes 3 aspects of reading letters, reading syllables and reading words that need to be improved. Through the application of media gamifikasi autistic children are taught interactively to improve the ability to read the beginning and give stimulus to children to do the reading with the game fun. This research aims to examine the differences in the ability to read the beginning of children with low grade autism in special school before and after the application of gamification media. This study uses a quantitative approach to the type of pre-experimental study design and study design one group pretest posttest design. The subjects of the study were 7 students of low grade autistic children whose initial reading ability still needs to be improved. Data were analyzed using Wilcoxon non-parametric statistical test. The results showed an increase that at the initial test or pre-test average obtained is 58.32 and given treatment after the final test or post-test average obtained is 79.75, this shows that there are significant differences. In addition, the results also show Zh = 2.36 greater than Zt = 1.96 with a critical value of 5% (two-sided test). If the Z count > Z table (2.36 > 1.96) shows that there are differences in the ability to read the beginning of autistic children in special schools before and after the application of gamification media.   Keywords: Gamification media, read the beginning